Solar half-piece battery and preparation method and application thereof
UV laser oxidation treatment and alumina thin film deposition technology to repair the interface defects at the edge of the solar half-cell, solve the problem of reduced battery efficiency and reliability after cutting, and significantly improve the power and stability of the battery and components.
Patent Information
- Application Number
- CN202411300740.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
The edge surface interface defects and impurities generated after the cutting of the solar half-cell lead to a reduction in battery efficiency and reliability, and a repair method is needed to improve battery efficiency and component power.
UV laser oxidation treatment was used to repair the interface defects on the edge surface of the battery after slice, and alumina film was deposited on the cutting surface, which enhanced the chemical passivation and field passivation effects through annealing treatment.
It significantly improves the power and stability of solar half-cell and its components, improves the flatness and continuity of the edges of the battery, reduces electrical recombination and leakage, and enhances the reliability of the battery.
Smart Images

Figure BDA0005047583970000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a solar half-cell and a preparation method and application thereof. Background Art
[0002] Solar cell half-cut cells have become the mainstream in the industry because they can reduce current, lower resistance, and increase module voltage. However, solar cell slicing also raises some new problems: (1) After cutting half or multiple solar cells, new edges will be generated, and cutting will destroy the interface characteristics of the edge surface of the solar cell half-cut cell; (2) Defects may be generated near the cut surface and introduce impurities. Defects and impurities form carrier recombination centers, which reduce the minority carrier lifetime; (3) If the exposed new edge is not passivated, it will cause efficiency loss and reliability degradation, thereby reducing the battery electrical performance. Therefore, there is an urgent need for a method that can repair the interface defects of the edge of the solar cell half-cut cell and improve the battery efficiency and module power. Summary of the invention
[0003] Based on this, it is necessary to provide a solar half-cell and its preparation method and application to address the above problems. The preparation method provided by the present invention effectively repairs the interface defects on the edge surface of the cell after slicing, and at the same time enhances the chemical passivation effect and field passivation effect of the edge of the solar half-cell, greatly improves the power of the solar half-cell and its components, and improves the stability and reliability of the solar half-cell and its components, and has broad application prospects.
[0004] A method for preparing a half-cell solar cell comprises the following steps:
[0005] The cut surface of the solar cell slice is subjected to ultraviolet laser oxidation treatment, wherein the power of the ultraviolet laser oxidation treatment is 40W to 80W, and the laser processing speed is 40m / s to 60m / s;
[0006] The solar cell slices after the ultraviolet laser oxidation treatment are subjected to surface pretreatment, and an aluminum oxide film is deposited on the cut surface, followed by annealing treatment to obtain a solar half-cell.
[0007] In one of the embodiments, in the step of ultraviolet laser oxidation treatment, the laser is selected from ultraviolet nanosecond laser or ultraviolet picosecond laser.
[0008] In one of the embodiments, in the pretreatment step, water vapor and protective gas are introduced in sequence for purging.
[0009] In one embodiment, the time for passing water vapor for purging and the time for passing protective gas for purging are each independently selected from 10s to 30s;
[0010] And / or, introducing water vapor and protective gas in sequence is regarded as one cycle, and the number of cycles is 5 to 30 times.
[0011] In one of the embodiments, in the step of depositing the aluminum oxide film, an atomic layer deposition method is adopted, and trimethylaluminum and water vapor are introduced in sequence for deposition, and after the step of introducing trimethylaluminum and the step of introducing water vapor, a protective gas is introduced for purging.
[0012] In one embodiment, the time for passing trimethylaluminum for deposition and the time for passing water vapor for deposition are independently selected from 2s to 15s, and the time for passing protective gas for purging is 10s to 30s;
[0013] And / or, introducing trimethylaluminum, protective gas, water vapor and protective gas in sequence is regarded as one cycle, and the number of cycles is 20 to 50 times.
[0014] In one of the embodiments, in the step of depositing the aluminum oxide film, the deposition temperature is 200°C to 350°C.
[0015] In one of the embodiments, the annealing treatment adopts a light injection annealing process, the temperature of the light injection annealing process is 600° C. to 700° C., and the mesh belt speed is 10000 mm / min to 16000 mm / min.
[0016] A solar half-cell manufactured by the method for manufacturing a solar half-cell as described above.
[0017] A photovoltaic module comprises the solar half-cell as described above.
[0018] The above-mentioned preparation method firstly performs laser oxidation repair on the cut surface of the solar cell slice by ultraviolet laser of specific power and processing speed, thereby repairing the interface defects on the edge surface of the cell after slicing; then, the cut surface is passivated by a pretreatment process and an aluminum oxide thin film deposition process, thereby improving the flatness and continuity of the passivation film, enhancing the chemical passivation and field passivation effects at the edge of the cell, reducing the electrical recombination and leakage phenomena at the edge of the cell, significantly improving the power of the solar half-cell and its components, and improving the stability and reliability of the solar half-cell and its components, and has broad application prospects. DETAILED DESCRIPTION
[0019] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0021] The method for preparing a half-cell solar cell provided by the present invention comprises the following steps:
[0022] The cut surface of the solar cell slice is subjected to ultraviolet laser oxidation treatment, wherein the power of the ultraviolet laser oxidation treatment is 40W to 80W, and the laser processing speed is 40m / s to 60m / s;
[0023] The solar cell slices after the ultraviolet laser oxidation treatment are subjected to surface pretreatment, and an aluminum oxide film is deposited on the cut surface, followed by annealing treatment to obtain a solar half-cell.
[0024] The above-mentioned preparation method firstly performs laser oxidation repair on the cut surface of the solar cell slice by ultraviolet laser of specific power and processing speed, thereby repairing the interface defects on the edge surface of the cell after slicing; then, the cut surface is passivated by a pretreatment process and an aluminum oxide thin film deposition process, thereby improving the flatness and continuity of the passivation film, enhancing the chemical passivation and field passivation effects at the edge of the cell, reducing the electrical recombination and leakage phenomena at the edge of the cell, significantly improving the power of the solar half-cell and its components, and improving the stability and reliability of the solar half-cell and its components, and has broad application prospects.
[0025] It can be understood that in the ultraviolet laser oxidation treatment, the power of the laser includes but is not limited to any value among 40W, 41W, 43W, 45W, 48W, 50W, 52W, 55W, 58W, 60W, 70W, 80W or a range between any two of them, and the processing speed includes but is not limited to any value among 40m / s, 41m / s, 43m / s, 60m / s or a range between any two of them.
[0026] In order to further improve the density of the formed silicon oxide film, improve the effect of repairing the interface defects at the edge of the cell after slicing, and further improve the efficiency of the solar half-cell and the power of the component, the power of the ultraviolet laser oxidation treatment is preferably 40W to 60W, and the laser processing speed is preferably 40m / s to 55m / s.
[0027] It should be noted that the present invention has no special restrictions on the thickness of the silicon oxide film formed by the ultraviolet laser oxidation treatment. Preferably, the thickness of the silicon oxide film is 1nm to 5nm, including but not limited to any point value of 1nm, 2nm, 3nm, 4nm, 5nm or a range value between any two of them; the surface of the silicon oxide film is relatively rough, and the roughness of the silicon oxide film is reduced through a subsequent pretreatment process to improve the flatness and continuity of the silicon oxide film, thereby improving the effect of repairing the edge interface defects of the battery after slicing.
[0028] Specifically, the sliced solar cells are placed horizontally, with the cut surfaces of the solar cell slices all facing the same side, stacked neatly, and placed in a material box; the material box together with the solar cell slices therein is placed in an ultraviolet laser device, the cut surfaces of the cells are scanned with an ultraviolet laser, and ultraviolet laser oxidation is performed.
[0029] It should be noted that the present invention has no special limitation on the solar cell, for example, crystalline silicon solar cells such as TOPCon solar cells, PERC solar cells, and IBC solar cells.
[0030] In one embodiment, in the step of ultraviolet laser oxidation treatment, the laser is selected from ultraviolet nanosecond laser or ultraviolet picosecond laser.
[0031] In one embodiment, in the pretreatment step, water vapor and protective gas are introduced sequentially for purging, which is beneficial to promote the formation of silicon oxide film, improve the flatness and continuity of the silicon oxide film, and thus improve the effect of repairing the edge interface defects of the cell after slicing. It can be understood that water vapor is introduced for purging for a period of time, and then protective gas is introduced for purging for a period of time.
[0032] Specifically, the protective gas is selected from nitrogen, helium, argon, etc. The present invention has no special limitation on this, and those skilled in the art can select it according to actual needs.
[0033] Specifically, the time for passing water vapor for purging and the time for passing protective gas for purging are independently selected from 10s to 30s. It can be understood that the time for passing water vapor for purging and the time for passing protective gas for purging can be the same or different.
[0034] In order to further improve the flatness and continuity of the silicon oxide film, it is preferred to circulate water vapor and protective gas for purging, with the introduction of water vapor and protective gas as one cycle, and the number of cycles is preferably 5 to 30 times. The number of cycles includes but is not limited to any point value among 5 times, 7 times, 10 times, 12 times, 15 times, 18 times, 20 times, 25 times, 28 times, 30 times or any range value between two of them.
[0035] It can be understood that, in different numbers of cycles, the time for introducing water vapor for purging may be the same or different, and the time for introducing protective gas for purging may be the same or different. For example, in the first cycle and the third cycle, the time for introducing water vapor for purging and / or the time for introducing protective gas for purging may be the same or different.
[0036] In one embodiment, in the step of depositing the aluminum oxide film, an atomic layer deposition method is adopted, and trimethylaluminum and water vapor are introduced in sequence for deposition, and after the step of introducing trimethylaluminum and the step of introducing water vapor, a protective gas is introduced for purging, which is beneficial to improve the continuity, flatness and continuity of the deposited aluminum oxide film, further enhance the chemical passivation and field passivation effects at the edge of the battery, reduce the electrical recombination and leakage phenomena at the edge of the battery, thereby improving the power of the solar half-cell and its components, and at the same time, improving the stability and reliability of the solar half-cell and its components.
[0037] It should be noted that the atomic deposition equipment used in the deposition method of the present invention is a commonly used equipment in the art, and the present invention will not elaborate on it.
[0038] Specifically, the time for introducing trimethylaluminum and water vapor for deposition is independently selected from 2s to 15s, and the time for introducing protective gas for deposition is 10s to 30s. It can be understood that the time for introducing trimethylaluminum for deposition and the time for introducing water vapor for deposition can be the same or different.
[0039] In order to further improve the flatness and continuity of the deposited Al2O3 film, it is preferred to cyclically introduce trimethylaluminum and water vapor for deposition, with the introduction of trimethylaluminum, protective gas, water vapor and protective gas as one cycle, and the number of cycles is 20 to 50. The number of cycles includes but is not limited to any point value among 20 times, 22 times, 25 times, 30 times, 33 times, 35 times, 40 times, 45 times, 48 times, 50 times or any range value between two of them.
[0040] It can be understood that, in different numbers of cycles, the time for introducing trimethylaluminum, protective gas, water vapor, and protective gas may be the same or different, and in the same cycle, the time for introducing the protective gas for purging twice may be the same or different. For example, in the first cycle and the third cycle, the time for introducing trimethylaluminum, protective gas, water vapor, and protective gas may be the same, or the time for introducing some gases may be different, or the time for introducing the four gases may be different.
[0041] It should be noted that the pretreatment process and the aluminum oxide film deposition process are both carried out in an atomic deposition device. Specifically, the material box together with the solar cell slices after ultraviolet laser oxidation are placed in the atomic deposition device for pretreatment and aluminum oxide film deposition in sequence.
[0042] Preferably, in the step of depositing the aluminum oxide film, the deposition temperature is 200°C to 350°C.
[0043] It can be understood that in the pretreatment step, the temperature is also 200°C to 350°C.
[0044] In one embodiment, the annealing treatment adopts a light injection annealing process, the temperature of the light injection annealing process is 600° C. to 700° C., and the mesh belt speed is 10000 mm / min to 16000 mm / min.
[0045] It should be noted that the light injection equipment used in the light injection annealing process of the present invention is a commonly used equipment in the art, and the present invention will not elaborate on it.
[0046] The present invention also provides a solar cell half-cut cell made by the above-mentioned method for making a solar cell half-cut cell. The solar cell half-cut cell of the present invention has high efficiency, excellent stability and reliability, and has broad application prospects.
[0047] The present invention also provides a photovoltaic module, comprising the solar half-cell as described above. The photovoltaic module of the present invention has high efficiency, excellent stability and reliability, and has broad application prospects.
[0048] Hereinafter, the solar half-cell and its preparation method and application will be further described through the following specific embodiments.
[0049] Example 1
[0050] Place the sliced TOPCon solar cells horizontally with all the cut surfaces facing the same side, stack them neatly and put them into a material box; put the material box together with the TOPCon solar cell slices into an ultraviolet laser device. The laser is an ultraviolet picosecond laser. The ultraviolet picosecond laser is used to scan the cut surfaces of the TOPCon solar cell slices and perform laser oxidation. The laser power is 45W and the laser processing speed is 45m / s.
[0051] The material box together with the TOPCon solar cell slices after UV laser oxidation are placed in an atomic layer deposition (ALD) device, and a pretreatment process is first performed. Water vapor is first introduced into the ALD device for 15 seconds, and then nitrogen is introduced for 15 seconds. This is one cycle, and the cycle is repeated 10 times. Then, aluminum oxide film is deposited. Trimethylaluminum (TMA) is first introduced into the ALD device for 10 seconds, and then nitrogen is introduced for 15 seconds. Water vapor is introduced for 10 seconds, and then nitrogen is introduced for 15 seconds. This is one cycle, and the cycle is repeated 40 times. The deposition temperature is 200°C.
[0052] The deposited TOPCon solar cell slices are taken out from the ALD device and then placed in a light injection device for annealing. The temperature in the light injection device is 620°C and the belt speed is 13000mm / min to obtain a TOPCon solar half-cell with edge repair.
[0053] Example 2
[0054] Place the sliced TOPCon solar cells horizontally with all the cut surfaces facing the same side, stack them neatly and put them into a material box; put the material box together with the TOPCon solar cell slices into an ultraviolet laser device. The laser is an ultraviolet picosecond laser. The ultraviolet picosecond laser is used to scan the cut surfaces of the TOPCon solar cell slices and perform laser oxidation. The laser power is 40W and the laser processing speed is 40m / s.
[0055] The material box together with the TOPCon solar cell slices after UV laser oxidation are placed in an atomic layer deposition (ALD) device, and a pretreatment process is first performed. Water vapor is first introduced into the ALD device for 15 seconds, and then nitrogen is introduced for 15 seconds. This is one cycle, and the cycle is repeated 10 times; then aluminum oxide film is deposited. Trimethylaluminum (TMA) is first introduced into the ALD device for 10 seconds, and then nitrogen is introduced for 15 seconds. Water vapor is introduced for 10 seconds, and then nitrogen is introduced for 15 seconds. This is one cycle, and the cycle is repeated 50 times. The deposition temperature is 200°C.
[0056] The deposited TOPCon solar cell slices are taken out from the ALD device and then placed in a light injection device for annealing. The temperature in the light injection device is 600°C and the belt speed is 16000mm / min to obtain edge-repaired TOPCon solar half-cells.
[0057] Example 3
[0058] Place the sliced TOPCon solar cells horizontally with all the cut surfaces facing the same side, stack them neatly and put them into a material box; put the material box together with the TOPCon solar cell slices into an ultraviolet laser device. The laser is an ultraviolet nanosecond laser. The cut surfaces of the TOPCon solar cell slices are scanned with the ultraviolet nanosecond laser and laser oxidation is performed. The laser power is 60W and the laser processing speed is 60m / s.
[0059] The material box together with the TOPCon solar cell slices after UV laser oxidation are placed in an atomic layer deposition (ALD) device, and a pretreatment process is first performed. Water vapor is first introduced into the ALD device for 15 seconds, and then nitrogen is introduced for 15 seconds. This is one cycle, and the cycle is repeated 30 times. Then, aluminum oxide film is deposited. Trimethylaluminum (TMA) is first introduced into the ALD device for 10 seconds, and then nitrogen is introduced for 15 seconds. Water vapor is introduced for 10 seconds, and then nitrogen is introduced for 15 seconds. This is one cycle, and the cycle is repeated 20 times. The deposition temperature is 350°C.
[0060] The deposited TOPCon solar cell slices are taken out from the ALD device and then placed in a light injection device for annealing. The temperature in the light injection device is 700°C and the belt speed is 10,000 mm / min to obtain edge-repaired TOPCon solar half-cells.
[0061] Example 4
[0062] The difference between Example 4 and Example 1 is that the laser power is 80W.
[0063] Comparative Example 1
[0064] The difference between Comparative Example 1 and Example 1 is that the laser power is 30 W and the laser processing speed is 45 m / s.
[0065] Comparative Example 2
[0066] The difference between Comparative Example 2 and Example 1 is that the laser power is 45 W and the laser processing speed is 35 m / s.
[0067] Comparative Example 3
[0068] The difference between Comparative Example 3 and Example 1 is that the sliced TOPCon solar cells are not subjected to ultraviolet laser oxidation treatment, but are directly subjected to pretreatment and deposition of aluminum oxide film.
[0069] Comparative Example 4
[0070] The difference between Comparative Example 4 and Example 1 is that the sliced TOPCon solar cells are only subjected to ultraviolet laser oxidation treatment without pretreatment and deposition of aluminum oxide film.
[0071] Comparative Example 5
[0072] The difference between Comparative Example 5 and Example 1 is that the TOPCon solar cells after slicing are not subjected to edge passivation treatment.
[0073] All the repaired TOPCon solar half-cells in Examples 1 to 4 and Comparative Examples 1 to 4, as well as the TOPCon solar half-cells in Comparative Example 5 were packaged into components, and then the power of the components was measured. The results are shown in Table 1.
[0074] Table 1
[0075]
[0076] According to the results in Table 1, under the same test conditions, it can be seen from the comparison between Examples 1 to 4 and Comparative Example 5 that the chemical passivation and field passivation effects of the TOPCon solar half-cell after edge passivation provided by Examples 1 to 4 are better, and the power of the TOPCon solar cell module is at least increased by 2.7W. However, the results of Comparative Examples 1 to 4 show that the power of the TOPCon solar cell module is significantly lower than that of Examples 1 to 4, and the laser power and processing speed of the ultraviolet laser oxidation treatment are more important for the repair effect of the edge of the solar cell slice, and when the ultraviolet laser oxidation treatment is performed alone or the aluminum oxide film is deposited alone to repair the edge of the solar cell slice, the repair effect is poor and the passivation effect is poor. Therefore, the edge passivation method provided by the present invention can effectively repair the interface defects on the edge surface of the cell after slicing, while enhancing the chemical passivation effect and field passivation effect of the cell edge, greatly improving the power of the solar half-cell and its components, and improving the stability and reliability of the solar half-cell and its components, and has a wide range of application prospects.
[0077] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a half-cell solar cell, characterized in that: The preparation method comprises the following steps: The cut surface of the solar cell slice is subjected to ultraviolet laser oxidation treatment, wherein the power of the ultraviolet laser oxidation treatment is 40W to 80W, and the laser processing speed is 40m / s to 60m / s; The solar cell slices after the ultraviolet laser oxidation treatment are subjected to surface pretreatment, and an aluminum oxide film is deposited on the cut surface, followed by annealing treatment to obtain a solar half-cell.
2. The method for preparing a half-cell solar cell according to claim 1, characterized in that: In the step of ultraviolet laser oxidation treatment, the laser is selected from ultraviolet nanosecond laser or ultraviolet picosecond laser.
3. The method for preparing a half-cell solar cell according to claim 1, characterized in that: In the pretreatment step, water vapor and protective gas are introduced in sequence for purging.
4. The method for preparing a half-cell solar cell according to claim 3, characterized in that: The time for passing water vapor for purging and the time for passing protective gas for purging are each independently selected from 10s to 30s; And / or, introducing water vapor and protective gas in sequence is regarded as one cycle, and the number of cycles is 5 to 30 times.
5. The method for preparing a half-cell solar cell according to claim 1, characterized in that: In the step of depositing the aluminum oxide film, an atomic layer deposition method is adopted, trimethylaluminum and water vapor are introduced in sequence for deposition, and after the step of introducing trimethylaluminum and the step of introducing water vapor, a protective gas is introduced for purging.
6. The method for preparing a half-cell solar cell according to claim 5, characterized in that: The time for passing trimethylaluminum for deposition and the time for passing water vapor for deposition are each independently selected from 2s to 15s, and the time for passing protective gas for purging is 10s to 30s; And / or, introducing trimethylaluminum, protective gas, water vapor and protective gas in sequence is regarded as one cycle, and the number of cycles is 20 to 50 times.
7. The method for preparing a half-cell solar cell according to claim 5, characterized in that: In the step of depositing the aluminum oxide film, the deposition temperature is 200°C to 350°C.
8. The method for preparing a half-cell solar cell according to claim 1, characterized in that: The annealing treatment adopts a light injection annealing process, the temperature of the light injection annealing process is 600° C. to 700° C., and the mesh belt speed is 10000 mm / min to 16000 mm / min.
9. A solar half-cell manufactured by the method for manufacturing a solar half-cell according to any one of claims 1 to 8.
10. A photovoltaic module, characterized in that: Comprising the solar half-cell as claimed in claim 9.
Citation Information
Cited By
Solar cell and preparation method thereof, laminated cell and photovoltaic module
CN121442822A
